Is Fine Arts Inevitable Requisite for Bachelors Degree in Visual Arts?: Notes from the Admission Policy of a Nigerian University - Ajibade, Babson; Enamhe, Bojor; Oloidi, Wole (Richtmann Publishing, 2011)
There was dearth of students for the BA programme of the Department of Visual Arts and Technology, Cross RiverUniversity of Technology, Calabar, because a credit pass in fine arts at the secondary school level was requisite for admissions. Thisresearch sort to find out if doing fine arts at the secondary school level was an inevitable requisite for studying visual arts in the university.Admissions data was recorded for 6 years before, and 5 years after credit pass in fine arts was delisted as admission requisite. Researchinstruments were designed and applied to students and staff to find out if not having done fine arts in secondary school affected the abilityof BA students to learn and execute creative skills, or whether there was any significant difference in performance between them and thosethat did fine arts in secondary school. Data indicates a dramatic rise in the number of students that applied and were admitted after finearts was delisted. Further, 91.2% of the students were satisfied with doing visual arts without having done fine arts in secondary school,while 78.4% of the students and 100% of lecturers perceived no significant difference in performance between students that did fine arts insecondary school and those that did not. The study then concluded that fine arts is not an inevitable requisite for Bachelors Degree inVisual Arts and students that did not do the subject in secondary school can do as well if the curriculum and training conditions areright.